2019
DOI: 10.1111/jam.14407
|View full text |Cite
|
Sign up to set email alerts
|

Activity evaluation of pure and doped zinc oxide nanoparticles against bacterial pathogens andSaccharomyces cerevisiae

Abstract: Aims: This work aimed to evaluate the antimicrobial activity of pure (ZnO) and doped (ZnMgO) zinc oxide (ZnO) nanoparticles on bacterial pathogens and Saccharomyces cerevisiae to confirm their applicability as an alternative to antibiotics and to estimate their biocompatibility. Methods and Results: Microbial growth inhibition on agar plates, microbial viability and adaptation tests in broth with ZnO nanoparticles, spore germination, random amplified polymorphic DNA and SDS-PAGE analysis were conducted to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…Metal and metal‐oxide NPs exhibit different antibacterial efficiencies toward Gram‐positive and Gram‐negative bacteria, and may even have different effects on the bacterial strains within the same Gram‐positive or Gram‐negative group (Auger et al., 2018; Cavassin et al., 2015; Zanet et al., 2019). This effect originates probably from the presence of various membrane components in different bacteria that are the first barrier and the first target for NPs.…”
Section: Nanofillersmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal and metal‐oxide NPs exhibit different antibacterial efficiencies toward Gram‐positive and Gram‐negative bacteria, and may even have different effects on the bacterial strains within the same Gram‐positive or Gram‐negative group (Auger et al., 2018; Cavassin et al., 2015; Zanet et al., 2019). This effect originates probably from the presence of various membrane components in different bacteria that are the first barrier and the first target for NPs.…”
Section: Nanofillersmentioning
confidence: 99%
“…The dynamic role of ZnO NPs in food preservation entails the production of ROS, especially hydrogen‐peroxide in the presence of light (Auger et al., 2019; Vidic et al., 2013). Their antibacterial efficiency was shown for a broad range of microorganisms such as B. subtilis , S. aureus , E. coli , Salmonella , P. aeruginosa , C. jejuni (Auger et al., 2019; Stankic et al., 2016; Vidic et al., 2013; Zanet et al., 2019). Indeed, a greater sensitivity to H 2 O 2 was observed in bacteria that were more sensitive to ZnO NPs (d’Água et al., 2018).…”
Section: Nanofillersmentioning
confidence: 99%
“…ZnO has a wide range of applications because of its strong optical, electrical, piezoelectrical, semiconducting, and chemical sensing capabilities [ 64 , 65 ]. It was observed that increased antibiotic resistance of bacteria, its mutation, and unavailability of vaccine causes many health hazards to human beings.…”
Section: Metal Oxide Nanoparticles For Food Packaging Applicationmentioning
confidence: 99%
“…Bacteria remain the most commonly detected pathogen with metal oxide based electrochemical biosensors. Moreover, current trends are focused on the use of metal oxide photocatalytic properties in inactivation and elimination of bacteria [67][68][69][70]. For instance, a multifunctional electrochemical platform was obtained by combining ZnO, colloidal Ag and vancomycin [71].…”
Section: Metal Oxide Nanomaterialsmentioning
confidence: 99%